2022
DOI: 10.3390/agronomy12081969
|View full text |Cite
|
Sign up to set email alerts
|

Seed Characteristics Affect Low-Temperature Stress Tolerance Performance of Rapeseed (Brassica napus L.) during Seed Germination and Seedling Emergence Stages

Abstract: Screening and breeding elite varieties with rapid germination and uniform seedling emergence under low temperature is an effective strategy to deal with the cold climate occurring under late sowing conditions in the Yangtze River basin. This study focused on the performance of seven functional traits, including percentage of germination, percentage of emergence, mean germination time, mean emergence time, total seedling length, total dry weight, and seedling vigor index of 436 natural rapeseed populations unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Therefore, GSL and EA can be considered as promising agents for enhancing the drought tolerance of LGLE seeds during the germination stage. Additionally, a previous study reported that priming with GSL and EA improved stress tolerance at the rapeseed seedling stage [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, GSL and EA can be considered as promising agents for enhancing the drought tolerance of LGLE seeds during the germination stage. Additionally, a previous study reported that priming with GSL and EA improved stress tolerance at the rapeseed seedling stage [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the works of Sikorska et al [58] and Malhi et al [59], the plants from field experiments did not react to foliar fertilization with a greater seed yield. In multiple cases [60][61][62] in field and controlled trials, the abiotic conditions influenced the thousand seed weight, seed yield, seed germination, and seedling emergence of canola. In our work, despite the negative effect of the weather on PHA, NL, NS, and OC, the treatments increased these parameters.…”
Section: The First Growing Seasonmentioning
confidence: 99%
“…Generally, the response and sensitivity of crops to low temperatures depend on the growth stage [8,9]. The suitable germination temperature for soybean is approximately 30 • C, but the germination rate (GR) can be 50% at 17 • C [10].…”
Section: Introductionmentioning
confidence: 99%